Building a sustainable framework for laboratory animal welfare and ethics education: challenges and reform strategies - Zhang, Jian; Zhang, Lingyan (Frontiers in Veterinary Science, 2025)
China has established a relatively comprehensive laws and regulations for laboratory animal welfare and ethics (LAWE). In accordance with regulatory requirements, most institutions have set up institutional animal care and use committee (IACUC) to conduct ethical reviews of laboratory animal welfare. The majority of students demonstrate a high level of awareness of LAWE. However, they often lack comprehensive knowledge of the related principles and struggle to apply them in practice. This paper identifies four core challenges for LAWE education: (1) disjointed curricula; (2) undertrained faculty; (3) weak institutional safeguards; and (4) an underdeveloped ethical culture. To address these issues, we propose a comprehensive reform framework across four dimensions: (1) developing a “Required + Integrated + Tiered” curriculum system that combines theory with practice; (2) establishing a dual-certification mechanism and continuous training for faculty to ensure both ethical and technical competence; (3) implementing a closed-loop governance model including entry thresholds, robust IACUC review, and ongoing oversight; and (4) fostering a campus-wide ethical ecosystem through rituals, peer support, and public engagement. These reforms aim to embed ethical awareness into the entire educational process, cultivate respect for life, and build a sustainable, high-quality biomedical education system rooted in both scientific rigor and humanistic values.